Mathematical Modeling Of The Active Life Expectancy Among The Famous Soviet Mathematicians - P. V. Gerasimenko (Здоровье мегаполиса, 2024)
The author carried out the mathematical modeling of the longevity index among the famous mathematicians who had most of active life years during the existence of the Soviet Union. Based on a sample of statistical data, the probability distribution and density functions for the longevity of mathematicians who were born or worked in the Soviet Union were created. Modeling was done using polynomial functions through the Excel regression analysis tool. A comparative analysis of the probability distribution functions for the longevity of famous Soviet mathematicians and mathematicians who lived in different countries in the 20th century was performed.